Pengaruh Promosi Penjualan Terhadap Repurchase Intention yang Dimediasi Oleh Customer Satisfaction Pada Fore Coffee Suhat (Studi Masyarakat Kec. Lowokwaru Kota Malang) - Sofianti, Widya Lisa; Rachma, N; Sholehuddin, Sulton (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of sales promotion on repurchase intention, mediated by customer satisfaction, among customers of Fore Coffee Suhat, Malang. The research employs a quantitative method and utilizes Partial Least Square – Structural Equation Modeling (SEM-PLS) analysis, with data collected through questionnaires distributed to Fore Coffee Suhat customers. The results indicate that sales promotion has a positive and significant effect on consumer repurchase intention and customer satisfaction. Additionally, customer satisfaction is proven to be a mediating variable that strengthens the relationship between sales promotion and repurchase intention. These findings provide managerial implications for Fore Coffee in designing more effective promotional strategies to enhance customer loyalty. Keywords: Sales Promotion, Repurchase Intention, Customer Satisfaction